The art of shapeshifting : facilitating strategic foresight to independent non-executive directors - a strategic approach to corporate governance in SA - Engelbrecht, Marianne (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--Stellenbosch University, 2012.